Multi-level swell voltage control for minimizing the damage to an on-grid system - Saktanong Wongcharoen; Sansak Deeon (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2020)
This article presented multi-level swell voltage control for minimizing the damage to an on-grid system between 1.3 to 1.8 pu. in compliance with the value regulated by IEEE and IEC standards. A window comparator circuit and comparator circuit with hysteresis transistor were used as the voltage detector and the excessive pulse entering the multi-level control of the load. According to the designed function in every stage in the form of fail-safe AND gate, the system was set for this case by turning to the fail-safe mode in order to prevent a fail-dangerous mode that might harm the electric system if the device in the detection circuit is deprived of qualification which is against the condition. Due to the Failure Mode and Effect Analysis (FMEA) in accordance with IEC-6196-1, the function prevents the electric and electronic devices of the on-grid system from damage. The design and installation of the electric protection device SVSS has a parallel-connect with the electric system without the concern of the load’s current.